Employment Probability Trajectories Up To 10 Years After Moderate-To-Severe Traumatic Brain Injury - Howe, Emilie I.; Andelic, Nada; Perrin, Paul B.; Røe, Cecilie; Sigurdardottir, Solrun; Arango-Lasprilla, Juan Carlos; Lu, Juan; Løvstad, Marianne; Forslund, Marit Vindal (Frontiers in Neurology, 2018)
Aims: To examine trajectories of employment probability up to 10 years following moderate-to-severe traumatic brain injury (TBI) and identify significant predictors from baseline socio-demographic and injury characteristics. Methods: A longitudinal observational study followed 97 individuals with moderate-to-severe TBI for their employment status up to 10 years post injury. Participants were enrolled at the Trauma Referral Center in South-Eastern Norway between 2005 and 2007. Socio-demographic and injury characteristics were recorded at baseline. Employment outcomes were assessed at 1, 2, 5 and 10 years. Hierarchical linear modelling was used to examine employment status over time and assess the predictors of time, gender, age, relationship status, education, employment pre-injury, occupation, cause of injury, acute Glasgow Coma Scale (GCS) score, duration of post-traumatic amnesia, CT findings, and injury severity score, as well as the interaction terms between significant predictors and time. Results: The linear trajectory of employment probabilities for the full sample remained at approximately 50% across 1, 2, 5- and 10-years post-injury. Gender (p = 0.016), relationship status (p = 0.002), employment (p <0.001) and occupational status at injury (p = 0.005), and GCS (p = 0.006) yielded statistically significant effects on employment probability trajectories. Male gender, those in a partnered relationship at the time of injury, individuals who had been employed at the time of injury, those in a white-collar profession, and participants with a higher acute GCS score had significantly higher overall employment probability trajectories across the four time points. The time*gender interaction term was statistically significant (p = 0.002), suggesting that employment probabilities remained fairly stable over time for men, but showed a downward trend for women. The time*employment at injury interaction term was statistically significant (p = 0.003), suggesting that employment probabilities were fairly level over time for those who were employed at injury, but showed an upward trend over time for those who had been unemployed at injury. Conclusion: Overall employment probability trajectories remained relatively stable between 1 and 10 years. Baseline socio-demographic and injury characteristics were predictive of employment trajectories. Regular follow-up is recommended for patients at risk of long-term unemployment.